Conjugated polyelectrolyte hole transport layer for inverted-type perovskite solar cells - Choi, Hyosung (Nature Pub. Group, 2015)
Organic–inorganic hybrid perovskite materials offer the potential for realization of low-cost and flexible next-generation solar cells fabricated by low-temperature solution processing. Although efficiencies of perovskite solar cells have dramatically improved up to 19% within the past 5 years, there is still considerable room for further improvement in device efficiency and stability through development of novel materials and device architectures. Here we demonstrate that inverted-type perovskite solar cells with pH-neutral and low-temperature solution-processable conjugated polyelectrolyte as the hole transport layer (instead of acidic PEDOT:PSS) exhibit a device efficiency of over 12% and improved device stability in air. As an alternative to PEDOT:PSS, this work is the first report on the use of an organic hole transport material that enables the formation of uniform perovskite films with complete surface coverage and the demonstration of efficient, stable perovskite/fullerene planar heterojunction solar cells.